Improved Endurance of Ferroelectric HfxZr1–xO2 Integrated on InAs Using Millisecond Annealing. Issue 27 (23rd August 2022) - Athle, Robin; Blom, Theodor; Irish, Austin; Persson, Anton E. O.; Wernersson, Lars‐Erik; Timm, Rainer; Borg, Mattias
Abstract: Ferroelectric Hfx Zr1–x O2 (HZO) is typically achieved by crystallization of an amorphous thin film via rapid thermal processing (RTP) at time scales of seconds to minutes. For integration on III–V semiconductors, this approach can severely degrade the sensitive HZO/III–V interface. To evaluate whether a reduced thermal budget can improve the interface quality, millisecond duration thermal anneals are utilized using a flash lamp annealer (FLA) on HZO/InAs capacitors. Through thorough electrical characterization such as polarization hysteresis, endurance, and capacitance‐voltage measurements, as well as synchrotron‐based chemical interface characterization, the FLA and RTP treatments are compared and the FLA results are found in lower interface defect density and higher endurance, but also have generally lower remanent polarization ( Pr ) compared to RTP. Additionally, ways to achieve high Pr and low interface defect density using multiple lower energy flashes, as well as by pre‐crystallization during the ALD growth step are investigated. Using FLA, Pr exceeding 20 µC cm −2 is achieved, with extended endurance properties compared to RTP treatment and a considerably decreased defect density, indicative of a higher quality HZO/InAs interface. This work presents valuable insight into the successful integration of ferroelectric HZO on low thermal budget III–V semiconductors. Abstract : In order to enable ferroelectric HfZrO2 integration with III‐V semiconductors, this work highlights the benefits of crystallizing the oxide using millisecond flash lamp annealing where the annealing is performed 1000x faster than in traditional rapid thermal processing. This approach limits the decomposition of the thermally sensitive InAs substrate, improving the endurance of the devices.